Expression of TRPV1 channels by Cajal‐Retzius cells and layer‐specific modulation of synaptic transmission by capsaicin in the mouse hippocampus. (24th June 2018) - Anstötz, Max; Lee, Sun Kyong; Maccaferri, Gianmaria
Abstract : Key points: By taking advantage of calcium imaging and electrophysiology, we provide direct pharmacological evidence for the functional expression of TRPV1 channels in hippocampal Cajal‐Retzius cells. Application of the TRPV1 activator capsaicin powerfully enhances spontaneous synaptic transmission in the hippocampal layers that are innervated by the axons of Cajal‐Retzius cells. Capsaicin‐triggered calcium responses and membrane currents in Cajal‐Retzius cells, as well as layer‐specific modulation of spontaneous synaptic transmission, are absent when the drug is applied to slices prepared from TRPV1 − / − animals. We discuss the implications of the functional expression of TRPV1 channels in Cajal‐Retzius cells and of the observed TRPV1‐dependent layer‐specific modulation of synaptic transmission for physiological and pathological network processing. Abstract: The vanilloid receptor TRPV1 forms complex polymodal channels that are expressed by sensory neurons and play a critical role in nociception. Their distribution pattern and functions in cortical circuits are, however, much less understood. Although TRPV1 reporter mice have suggested that, in the hippocampus, TRPV1 is predominantly expressed by Cajal‐Retzius cells (CRs), direct functional evidence is missing. As CRs powerfully excite GABAergic interneurons of the molecular layers, TRPV1 could play important roles in the regulation of layer‐specific processing. Here, we have taken advantage of calcium imaging with the genetically encoded indicator GCaMP6s and patch‐clamp techniques to study the responses of hippocampal CRs to the activation of TRPV1 by capsaicin, and have compared the effect of TRPV1 stimulation on synaptic transmission in layers innervated or non‐innervated by CRs. Capsaicin induced both calcium responses and membrane currents in ∼50% of the cell tested. Neither increases of intracellular calcium nor whole‐cell currents were observed in the presence of the TRPV1 antagonists capsazepine/Ruthenium Red or in slices prepared from TRPV1 knockout mice. We also report a powerful TRPV1‐dependent enhancement of spontaneous synaptic transmission onto interneurons with dendritic trees confined to the layers innervated by CRs. In conclusion, our work establishes that functional TRPV1 is expressed by a significant fraction of CRs and we propose that TRPV1 activity may regulate layer‐specific synaptic transmission in the hippocampus. Lastly, as CR density decreases during postnatal development, we also propose that functional TRPV1 receptors may be related to mechanisms involved in CR progressive reduction by calcium‐dependent toxicity/apoptosis. Key points: By taking advantage of calcium imaging and electrophysiology, we provide direct pharmacological evidence for the functional expression of TRPV1 channels in hippocampal Cajal‐Retzius cells. Application of the TRPV1 activator capsaicin powerfully enhances spontaneous synaptic transmission in the hippocampal layers that are innervated by the axons of Cajal‐Retzius cells. Capsaicin‐triggered calcium responses and membrane currents in Cajal‐Retzius cells, as well as layer‐specific modulation of spontaneous synaptic transmission, are absent when the drug is applied to slices prepared from TRPV1 − / − animals. We discuss the implications of the functional expression of TRPV1 channels in Cajal‐Retzius cells and of the observed TRPV1‐dependent layer‐specific modulation of synaptic transmission for physiological and pathological network processing.